Production of amorphous silica from rice husk in fluidised bed system (penghasilan silika amorfus daripada sekam padi dengan sistem lapisan terbendalir) - Taib, Mohd. Rozainee; Ngo, Saik Peng (Faculty of Chemical and Natural Resource Engineering, 2007)

(untitled)
The objective of this research is to design and develop a pilot scale fluidized bed combustion system for the production of amorphous silica from rice husk. The scopes of the research include investigation of the basic combustion characteristics of rice husk, the optimum fluidisation, mixing and combustion parameters and also the optimum fluidised bed combustor design, to improve carbon burnout in siliceous ash product and to develop a pilot plant. Under this research, amorphous silica with very low residual carbon content (approximately 1.0wt% residual carbon) was successfully being produced. The optimum freeboard height to prevent sand contamination and to achieve complete carbon burnout in the rice husk ash was found to be at least 5000mm through computational fluid dynamics (CFD) modeling study. With the experimental and modeling results obtained, the pilot scale fluidized bed combustion system of âˆ…500mm x 6000mm has been successfully designed, fabricated, installed and commissioned for the production of amorphous silica from rice husk. However, due to time and budget constraints of this research, detailed combustion study has not been fully investigated for the production of amorphous products.